The Financial Crisis from a Forecaster's Perspective - Katja Drechsel; Rolf Scheufele (Kredit und Kapital, 2012)
The Financial Crisis from a Forecaster's Perspective This paper analyses the recession in 2008/2009 in Germany. This recession is very different from previous recessions in particular regarding their causes and magnitude. We show to what extent forecasters and forecasts based on leading indicators fail to detect the timing and the magnitude of the recession. This study shows that large forecast errors for both expert forecasts and forecasts based on leading indicators resulted during this recession which implies that the recession was very difficult to forecast. However, some leading indicators (survey data, risk spreads, stock prices) have indicated an economic downturn and hence, beat univariate time series models. Although the combination of individual forecasts provides an improvement compared to the benchmark model, the combined forecasts are worse than several individual models. A comparison of expert forecasts with the best forecasts based on leading indicators shows only minor deviations. Overall, the range for an improvement of expert forecasts in the crisis compared to indicator forecasts is small. (JEL E37, C53) – – Die Finanzkrise aus Sicht eines Prognostikers Dieser Beitrag untersucht die Rezession der Jahre 2008/2009 in Deutschland. Diese Rezession hebt sich in ihrer Ursache und Schwere deutlich von früheren Rezessionen ab. Es wird gezeigt, inwieweit Prognostiker und Prognosen basierend auf Frühindikatoren das Timing und die Stärke dieser Rezession verfehlt haben. Diese Studie deutet darauf hin, dass aufgrund der großen Prognosefehler bei Expertenprognosen und bei Prognosen basierend auf Frühindikatoren die Rezession sehr schwer zu prognostizieren war. Allerdings gibt es einige Frühindikatoren (Umfragedaten, Risikoaufschläge, Aktienpreise), die eine Wachstumsabschwächung prognostiziert haben und damit deutlich besser abschneiden als univariate Zeitreihenmodelle. Jedoch wurde insbesondere die Stärke nicht richtig eingeschätzt. Die Kombination einzelner Prognosemodelle bietet zwar eine Verbesserung zur Benchmarkprognose, schneidet aber schlechter ab als einige Einzelindikatormodelle. Vergleicht man die Expertenprognosen mit den besten Prognosen auf Basis von Frühindikatoren, so ist der Abstand relativ klein. Insgesamt ist der Spielraum einer Verbesserung der Expertenprognose in der Krise im Vergleich zu Indikatormodellen relativ gering.
Keywords: E37; C53; 330